On estimates of the remainder term in the central limit theorem - Bikelis, A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:A. Бикялис. Оценки остаточного члена в центральной предельной теоремеA. Bikelis. Liekamojo nario centrinėje ribinėje teoremoje įvertinimai